(untitled) (CAHIERS MAGELLANES-NS, 2024)
Background: One of the most serious dental public health concerns affecting children is traumatizeddental injuries (TDIs), which are frequently occurring in the general population. In order to effectivelymanage it, dental practitioners need to increase awareness of it. Aim: This cross-sectional studyaimed to assess elementary school staff members' attitudes and levels of knowledge on the first-aidmanagement of children's traumatic dental injuries in Saudi Arabia. Methods: A cross-sectional studyof self-administered questionnaire consisted of; demographic data, self-assessment, knowledge andattitude, were collected from elementary school staff members from all five regions (The eastern,western, northern, southern and central). Result: As regard the participants’ knowledge towardstraumatic dental injuries management in children, a vast majority, 86.3%, acknowledge the critical roleof time in saving a tooth. Furthermore, the majority view dental trauma management as an emergency(77.3%). The role of teachers in saving a tooth during school dental injuries is considered important by81.6% of respondents. Additionally, 75.4% advocate for teacher involvement to ensure timelyassistance. The data also addresses the issue of mandating mouth guards in outdoor sports, with 61.5%in favor of compulsion. A substantial majority (83.9%) support the idea of providing training in dentaltrauma management. Regarding attitude of participants towards traumatic dental injuries managementin children, varied responses and perceptions have been revealed. The preference for pediatric dentistsin such situations was clear, along with the importance of seeking professional help promptly after toothloss. Storage methods for fallen teeth also varied, with a leaning towards saline solution and milk. Thestudy also revealed that the belief that managing the tooth injuries by the teachers is a moralresponsibility has statistically significant relation to education (p value=0.002), receiving first aidraining (p value=0.0001), and if the teacher witnessed a child fell over and got tooth injury (pvalue=0.002). It also shows statistically insignificant relation to gender, age, region of residence,nationality, workplace, position, and working experience. Conclusion: The findings revealed asignificant gap in teachers’ preparedness to handle dental trauma emergencies, with a majorityacknowledging the critical role of timely intervention, supporting the inclusion of tooth injurymanagement in teacher training, and recognizing the necessity for teacher involvement in ensuringtimely assistance. Varied responses and perceptions were observed regarding the type of teeth damaged,appropriate actions to take, and storage methods for fallen teeth, emphasizing the need forcomprehensive education and training programs.